Nutritional and sensory properties of smoked pork sausage produced with pig stomach as filler-meat - Akwetey, Worlah Yawo; Dorleku, Justice Bless; Yeboah, Elizabeth (International Journal of Agricultural Research, Innovation and Technology, 2022)
The nutritional and sensory characteristics of processed meat are of major concern to consumers across the globe. This study evaluated nutritional and sensory properties of pork sausages using pig stomach as filler meat. Pig stomach replaced lean pork at 0% (control), 25%, 50%, 75% and 100%, respectively to obtain treatments coded as T0, T25, T50, T75 and T100, respectively. The sausages were assessed for acidity, water holding capacity, cooking loss, proximate composition and sensory attributes. There were no significant differences (p>0.05) in flavour of sausages in particular; and all other sensory attributes of sausages produced with or without pig stomachs. Treatments T0, T25 and T50 were very similar in most of the sensory properties. Both pH and water holding capacity reduced with increasing levels of pig stomach used, and there were significant differences (p<0.05) between treatments. The results obtained suggest that pig stomach could be used at 50% in smoked pork sausages without adverse effects on nutritional and sensory properties. Int. J. Agril. Res. Innov. Tech. 12(1): 67-71, June 2022